2023
DOI: 10.3390/foods12193621
|View full text |Cite
|
Sign up to set email alerts
|

Combining Vis-NIR and NIR Spectral Imaging Techniques with Data Fusion for Rapid and Nondestructive Multi-Quality Detection of Cherry Tomatoes

Fei Tan,
Xiaoming Mo,
Shiwei Ruan
et al.

Abstract: Firmness, soluble solid content (SSC) and titratable acidity (TA) are characteristic substances for evaluating the quality of cherry tomatoes. In this paper, a hyper spectral imaging (HSI) system using visible/near-infrared (Vis-NIR) and near-infrared (NIR) was proposed to detect the key qualities of cherry tomatoes. The effects of individual spectral information and fused spectral information in the detection of different qualities were compared for firmness, SSC and TA of cherry tomatoes. Data layer fusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The near infrared hyperspectral imaging is applicable to solid samples as well as liquid samples, thus the variety of its applications in food technologies to a large range of food products. Several studies using the near infrared hyperspectral technology have contributed to various areas of food technologies including food quality control and authentication (18,19,20,21), food safety assessment (22,23,24,25), food process monitoring and optimization (26,27,28), food shelf-life prediction (29,30), food ingredients analysis (31,32), food allergens detection (33,34), and food sorting and grading (35). These research works showed that NIR-HSI covers notable areas of food technologies.…”
Section: Near Infrared Hyperspectral Imaging In Food Technologiesmentioning
confidence: 99%
“…The near infrared hyperspectral imaging is applicable to solid samples as well as liquid samples, thus the variety of its applications in food technologies to a large range of food products. Several studies using the near infrared hyperspectral technology have contributed to various areas of food technologies including food quality control and authentication (18,19,20,21), food safety assessment (22,23,24,25), food process monitoring and optimization (26,27,28), food shelf-life prediction (29,30), food ingredients analysis (31,32), food allergens detection (33,34), and food sorting and grading (35). These research works showed that NIR-HSI covers notable areas of food technologies.…”
Section: Near Infrared Hyperspectral Imaging In Food Technologiesmentioning
confidence: 99%
“…Thanks to these features, food plants can be automated and controlled in real time. It is very popular in the food industry due to its speed [8], objectivity and low cost [9][10][11][12][13][14]. It also has the advantage of being a non-destructive technique that allows for the entire production to be analysed [15,16].…”
Section: Introductionmentioning
confidence: 99%